On the Improvement of the Rules on the Obligation of Interpretation by Judges in Online Litigation - Guojian Zhang (Studies in Law and Justice, 2024)
As a new way of litigation, the practice of online litigation has attracted great attention, especially online civil litigation, which has also become a hot issue in the field of civil litigation. The online judge’s obligation to interpret not only inherits the content of the existing obligation of traditional offline litigation, but also expands the scope of the obligation of interpretation, and the expansion of the online judge’s obligation to interpret adapts to the requirements of online litigation following the principles of fairness and efficiency, convenience and benefit. However, the existing rules on online litigation are relatively general in their provisions on the obligation of interpretation by online judges, and judges usually enjoy a certain degree of discretion in the exercise of the obligation to interpret in online litigation, which makes there are some problems that need to be solved urgently in the performance of judges’ obligation to interpret in online litigation.